2021
DOI: 10.3233/efi-200448
|View full text |Cite
|
Sign up to set email alerts
|

Information-seeking behaviours of teacher students: A systematic review of qualitative methods literature

Abstract: Teachers are the key to an inclusive and quality education for all. Therefore, training teachers and teacher students and understanding how they learn, including information-seeking behaviours, is crucial. This systematic literature review explores the observed research gap regarding teacher students’ affective information-seeking behaviours. Of specific interest are the research practice context. Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guided the review process. Searches we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…This study makes a valuable contribution to the limited body of literature on emotions identified by researchers in information-seeking behaviour research in general (e.g. Krakowska, 2020; Lopatovska and Arapakis, 2011; Savolainen, 2015b) and regarding teacher students in particular (Dahlqvist, 2021a, b and 2022). Increased knowledge of the fundamentally important role emotions play in formal and higher education contexts, especially an in-depth understanding of the qualitative nuances and variations of primary teacher students' experienced appraisals and emotions in the process of achieving information-seeking skills.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This study makes a valuable contribution to the limited body of literature on emotions identified by researchers in information-seeking behaviour research in general (e.g. Krakowska, 2020; Lopatovska and Arapakis, 2011; Savolainen, 2015b) and regarding teacher students in particular (Dahlqvist, 2021a, b and 2022). Increased knowledge of the fundamentally important role emotions play in formal and higher education contexts, especially an in-depth understanding of the qualitative nuances and variations of primary teacher students' experienced appraisals and emotions in the process of achieving information-seeking skills.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is still a limited body of literature on emotions, as noted by several researchers (e.g. Dahlqvist, 2021a, b and 2022; Krakowska, 2020; Lopatovska and Arapakis, 2011; Savolainen, 2015a; Savolainen, 2015b). Despite this lack of research, there are several valuable LIS and IB contributions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Penelitian ini melibatkan siswa sekolah dasar sebagai subjek utama, mengambil pendekatan kualitatif untuk mengumpulkan data melalui observasi, wawancara, dan analisis dokumen (Appleton, 2018;Botelho, 2018;Dahlqvist, 2021;Mansfield, 2023;Roulston, 2021;Shekhar, 2019). Dengan demikian, penelitian ini tidak hanya akan memberikan gambaran mendalam tentang efektivitas metode bermain peran, tetapi juga akan mengungkapkan perubahan yang terjadi pada karakter peduli lingkungan siswa selama proses pembelajaran.…”
Section: Pendahuluanunclassified